Development of a methodology for property valuation using the retrospective method of correlation-regression dependence - Ilnur Failovitch Gareev; Timur Aleksandrovitch Akhmetgaliev (Недвижимость: экономика, управление, 2024)
The conducted research is based on information databases of real estate objects, where an important problem is that while there is a large amount of data, on the one hand, they are used for market research and mass valuation of real estate, but on the other hand, due to the lack of sufficient information or tools, do not allow to reflect the market situation fully.